Diseño y control de temperatura del laboratorio de nanomicrofluídica (2020)
The design and control of temperature of the nanomicrofluidic laboratory consists on the design of a system that recirculates water on a reservoir, where the water is heating on a temperature that is assigned by the user of the laboratory. Also, the temperature is assigned at a specific time, which influences the moment when the water starts to recirculate to the thermal chamber, where is located the microsystem. This project is aimed at the Andes University research group CMUA. The research group seeks to study the behavior of the microsystem when it is surrounded by water at a specific temperature (20°C - 60°C). At the same time, the system was designed with the purpose that the user can light up the thermal chamber during the test. As mentioned, the moment when water recirculation begins is essential to understand the behavior of the system. For this reason, the characterization methodology was carried out in accordance with the physical characteristics of the system and the requirements of the project. The characterization was carried out for seven different temperature ranges. For the established ranges, different times were assigned in which the recirculation of the water began, these moments depended on the temperature of the water in the reservoir. The results were analyzed, and the experimental uncertainty was the decision variable to select the best case. On the other hand, assigning the water temperature in the thermal chamber and turning on the lighting is done through the Raspberry Pi terminal. As a future work, it is required that the project be replicated with five thermal chambers, in this way the users could make simultaneous and independent tests.--Taken from the Degree Document Format.